2016
DOI: 10.1002/path.4752
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of miR‐455‐5p by the TGF‐β–SMAD signalling axis promotes the proliferation of oral squamous cancer cells by targeting UBE2B

Abstract: MicroRNAs (miRNAs) are involved in the tumourigenesis of various cancers by regulating their downstream targets. To identify the changes of miRNAs in oral squamous cell carcinoma (OSCC), we investigated the expression profiles of miRNAs in 40 pairs of OSCC specimens and their matched non-tumour epithelial tissues. Our data revealed higher miR-455-5p expression in the tumour tissues than in the normal tissues; the expression was also higher in oral cancer cell lines than in normal keratinocyte cell lines. MiR-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…To the best of our knowledge, only one study indicated that miR-455-5p was differentially expressed between invasive and non-invasive breast cancer based on the analyses of archived FFPE tissues and laboratory-based barcoded cDNA library 46 . In other cancers, miR-455-5p has been reported as a potential oncogene for non-small cell lung cancer 47 , colon cancer 48 and oral squamous cancer 49 . In our present study, we confirmed these 4 screened DEmiRNAs not only differentially expressed in TNBC cell lines compared to normal breast cell line, but also showed effective regulation on cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study indicated that miR-455-5p was differentially expressed between invasive and non-invasive breast cancer based on the analyses of archived FFPE tissues and laboratory-based barcoded cDNA library 46 . In other cancers, miR-455-5p has been reported as a potential oncogene for non-small cell lung cancer 47 , colon cancer 48 and oral squamous cancer 49 . In our present study, we confirmed these 4 screened DEmiRNAs not only differentially expressed in TNBC cell lines compared to normal breast cell line, but also showed effective regulation on cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-455 (miR-455) is recognized as a broadly conserved noncoding RNA that has been implicated in various cancers. The function of miR-455 has been confirmed in prostate cancer [51], gastric cancer [52], and oral squamous cancer cells [53]. However, the potential effect of miR-455-3p has rarely been explored in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays showed that miR-455-3p enhanced cell proliferative, invasive and migratory abilities in TNBC cell lines [28]. Furthermore, studies on non-small cell lung cancer [29], colon cancer [30] and oral squamous cancer cells [31] also verified that miR-455-5p may function as a potential oncogene. In addition, our study also showed exosomal miR-455-5p in breast cancer cells may influence the phenotype of neighboring or distant non-malignant recipient cells by decreasing the expression of CDKN1B gene.…”
Section: Figure 7 the Associations Between Differentially Expressed mentioning
confidence: 85%